ANALYSIS OF COMPLICATIONS OF SURGICAL TREATMENT OF THORACIC AND LUMBAR COMPRESSION FRACTURES IN ELDERLY PATIENTS - D.M.S.Norov A.U; Kholikov Sh. (Scholar Express Journals, 2022)
To study the causes of complications after surgical interventions for compression fractures of the thoracic and lumbar spine in adults and the elderly
Keywords: lumbar; spine; compression